Microarray Glycan Profiling Reveals Algal Fucoidan Epitopes in Diverse Marine Metazoans - Salmeán, Armando A.; Hervé, Cécile; Jørgensen, Bodil; Willats, William G. T.; Mravec, Jozef (Frontiers in Marine Science, 2017)
Despite the biological importance and pharmacological potential of glycans from marine organisms, there are many unanswered questions regarding their distribution, function and evolution. Here we describe microarray-based glycan profiling of a diverse selection of marine animals using antibodies raised against fucoidan isolated from a brown alga. We demonstrate the presence of two fucoidan epitopes in six animals belonging to three phyla including Porifera, Molusca and Chordata. We studied the spatial distribution of these epitopes in Cliona celata (‘boring sponge’) and identified their restricted localisation on the surface of internal chambers. Our results show the potential of high-throughput screening and probes commonly used in plant and algal cell wall biology to study the diversity and distribution of glycan structures in metazoans.